Academic Infrastructure and Student Satisfaction in Islamic Higher Education: Evidence from a Regression Study at UIN Sunan Kalijaga - Arlin Prima Sari; Ambar Wati; Na'im, Zam Zam Nur; Gibran, Mohammad Ghalil (Journal of Islamic Education Management Research, 2024)
Purpose – This study addresses the critical role of academic infrastructure in student satisfaction within Indonesian higher education, a context underexplored in existing literature. It examines whether facility availability at FITK UIN Sunan Kalijaga Yogyakarta significantly impacts student satisfaction, offering empirical insights to guide institutional policies. Key findings reveal infrastructure as a primary determinant of satisfaction, reinforcing its strategic importance in academic environments. Design/methods – A quantitative approach was employed, with data collected via a 5-point Likert-scale questionnaire administered to 83 students (2020 cohort) selected through probability sampling (Slovin formula, 10% margin of error). Validity and reliability were confirmed using Pearson correlation (r-count > 0.1818) and Cronbach’s alpha (α > 0.90). Normality testing (Kolmogorov–Smirnov, p = 0.20) and SPSS v29-supported simple linear regression analyzed the relationship between infrastructure (independent variable) and satisfaction (dependent variable). Findings – Regression analysis demonstrated a significant positive effect (Y = 5.826 + 1.528X, p < 0.001), with infrastructure explaining 70.9% of satisfaction variance. Hypothesis testing confirmed the effect (F-test: p = 0.001; t-test: t-calculated = 14.035 > t-table = 1.664). All instrument items were valid (r-count > 0.1818) and reliable (α = 0.903–0.970). Research implications/limitations – The single-faculty focus and cross-sectional design limit generalizability. Unexplained variance (29.1%) suggests unmeasured factors (e.g., teaching quality) may influence satisfaction, warranting broader variable inclusion in future studies. Practical implications – Institutions should prioritize infrastructure investment, aligning development with student feedback and enrollment growth. Policymakers can leverage these findings to enhance institutional competitiveness and retention, integrating facility upgrades into budget planning. Originality/value – This study contributes novel empirical evidence from Indonesia’s Islamic higher education context, employing robust methodological rigor. It underscores infrastructure’s strategic value, proposing longitudinal, multi-institutional research to validate findings and explore non-material satisfaction drivers.